2015
DOI: 10.1155/2015/606479
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Taste Receptor Signaling Network: Possible Implication for Cognitive Functioning

Abstract: Sweet taste receptors are transmembrane protein network specialized in the transmission of information from special “sweet” molecules into the intracellular domain. These receptors can sense the taste of a range of molecules and transmit the information downstream to several acceptors, modulate cell specific functions and metabolism, and mediate cell-to-cell coupling through paracrine mechanism. Recent reports indicate that sweet taste receptors are widely distributed in the body and serves specific function r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 152 publications
0
28
0
Order By: Relevance
“…All of these signal cascade components are commonplace for chemosensory transduction. Unlike TAS2R receptors, TAS1Rs cause intracellular signaling via gap junctions and paracrine communications that cause adjacent cells to translocate proteins for glucose transportation (Welcome et al, 2015 ). In fact, it was the identification of α-gustducin (Hofer et al, 1996 ), and later taste receptors themselves, in brush cells located in the stomach and intestine that confirmed the presence of taste receptors outside the mouth.…”
Section: Taste Receptorsmentioning
confidence: 99%
“…All of these signal cascade components are commonplace for chemosensory transduction. Unlike TAS2R receptors, TAS1Rs cause intracellular signaling via gap junctions and paracrine communications that cause adjacent cells to translocate proteins for glucose transportation (Welcome et al, 2015 ). In fact, it was the identification of α-gustducin (Hofer et al, 1996 ), and later taste receptors themselves, in brush cells located in the stomach and intestine that confirmed the presence of taste receptors outside the mouth.…”
Section: Taste Receptorsmentioning
confidence: 99%
“…Subjective sweetness and pleasantness ratings differed among the preloads; however, it is unlikely these factors were primary determinants of FI. It has been suggested that sweetness may increase appetite due to the stimulation of gut taste receptors [ 36 ]. Importantly however, although the fruit drink was rated significantly sweeter than cola, test meal and cumulative FI did not differ between these beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Another phenomenon captured in our study involves the possible mechanism by which sucralose exerts its effects on classical and nonclassical monocytes in healthy young adults. Sweet taste of sucralose and other caloric and noncaloric sweeteners is mediated by G protein-coupled receptors (GPCR) T1R1, T1R2, and T1R3 [38]. Sweet taste receptors were firstly described in the gut [39], enteroendocrine cells, and pancreas [40].…”
Section: Discussionmentioning
confidence: 99%